Benchmarking Dalam Lembaga Pendidikan - Suluri, Suluri (Universitas Negeri Surabaya, 2019)
Every country strives for quality education in its country. This business is not without an intention, but rather to prepare qualified national cadres. The successor of a quality nation is very necessary to maintain the dignity and dignity of a country. Therefore, national standard education quality assurance is a necessity of a country. educational institutions that provide educational services in their travels are very likely to be graduates (graduates) not in accordance with the minimum standards that have been formulated. So quality assurance is a necessity to provide satisfaction to customers. One of the quality assurance efforts in educational institutions is by benchmarking.